Current Status of Norovirus Infections in Children in Sub-Saharan Africa - Samuel Munalula Munjita (Journal of Tropical Medicine)
Noroviruses are a leading cause of acute sporadic gastroenteritis worldwide. In Sub-Saharan Africa, information regarding norovirus infections in children is scarce. A systematic review of studies performed between 1993 and June 2015 was conducted to establish the genotypic distribution and prevalence of norovirus infections in children (≤17) in Sub-Saharan Africa. Analysis of data from 19 studies involving 8,399 samples from children with symptomatic and nonsymptomatic gastroenteritis revealed prevalence of 12.6% (range 4.6% to 32.4%). The prevalence of norovirus infections was higher in symptomatic children (14.2%) than asymptomatic children (9.2%). Genogroup II (GII) was the most prevalent genogroup accounting for 76.4% of all the reported norovirus infections. The rest of the infections were GI (21.7%) and GI/GII (1.9%). The most common genotypes were GII.4 (65.2%), GI.7 (33.3%), and GI.3 (21.3%). These statistics were calculated from studies carried out in 12 out of 48 Sub-Saharan African countries. Therefore, more studies involving several countries are required to determine fully the epidemiology of noroviruses and their contribution to childhood diarrhoea in Sub-Saharan Africa.